Reflective practice as a means of critical thinking development in distance learning with university students - Liashenko, Iryna (Бердянський державний педагогічний університет, 2020)
Distance learning is getting one of the most popular and inevitable methods of learning and teaching nowadays, which insistently changes the vector in instructions. The education policy, nevertheless, is aimed to achiving the highest level in quality of learning and teaching, as the technologies are changing and requiring relevant level of professional competency, particularly, highly developed 21st-century skills from the graduate students. The teachers, practitioners, and university educators should look for efficient technologies in online learning, saving the students' motivation, and developing the important skills necessary for future professional development. The issue of finding the efficient ways in online learning is becoming one of the leading priorities in organization of the teaching and learning process. This study is sought to analyze the modern research sources about the effective methods teaching online not only develop critical thinking competency as an essential skill of professional portrait, but also enhance students' motivation to study. It also investigates the theoretical background related to reflective practice in university training, after that, it investigates the possible ways of applying reflective practice strategies as a tool for critical thinking skills development. The analysis of recent studies revealed the most sought-after ways of reflective practice strategies which can be widely used online. The result of the analysis provided support in favour of wide-spread methods, which proved their application in various experiments and practical implications, for example, e-portfolios, reflective journals, blogging, MOOCs, which significantly increase students' critical thinking. The implication of this study may be seen in practical development of online courses and assignments for students in todays' university educational process.
Рефлективна практика як засіб розвитку критичного мислення студентів університету в умовах дистанційного навчання
Дистанційне навчання є одним із найпопулярніших і неминучих методів навчання та викладання сьогодні, який наполегливо змінює вектор в освіті. Проте, освітня політика спрямована на досягнення найвищого рівня якості навчання та викладання, оскільки зі змінами технологій зростають вимоги до відповідного рівня професійної компетентності, зокрема, високо розвинених навичок 21-го століття у випускників. Викладачі університетів змушені підбирати ефективні технології для онлайн-навчання, щоб зберегти мотивацію студентів та розвинути важливі навички, необхідні для майбутнього професійного розвитку. Питання пошуку ефективних шляхів онлайн-навчання стає одним із провідних пріоритетів в організації процесу навчання. Це дослідження має на меті проаналізувати сучасні літературні джерела про ефективні методи дистанційного навчання не лише для розвитку компетентності критичного мислення як найважливіших навичок професійного портрету, але й для підвищення мотивації студентів до навчання. Робота також досліджує теоретичні передумови, пов'язані з рефлективною практикою в університетському навчанні, досліджує можливі способи застосування рефлективних практичних стратегій як інструменту розвитку навичок критичного мислення. Аналіз останніх досліджень виявив найбільш затребувані способи рефлективних практичних стратегій, які можна широко використовувати у дистанційному навчанні. Результат аналізу джерел виявив ряд розповсюджених методів, які довели практичну цінність застосування їх в різних експериментах та практичних наслідках, наприклад, електронних портфелях, рефлективних журналах, блогах, MOOC, що значно підвищує критичне мислення студентів. Практичне застосування цього дослідження можна побачити у практичній розробці онлайн-курсів та завдань для студентів у навчальному процесі сучасного університету.
Keywords: сritical thinking, distance learning, reflective practice, university students, critical thinking skills development; критичне мислення; дистанційне навчання, рефлективна практика, студенти університету, розвиток навичок критичного мислення